Differential Diagnosis of Parkinson Disease, Essential Tremor, and Enhanced Physiological Tremor with the Tremor Analysis of EMG - Jie Zhang; Yan Xing; Xiuli Ma; Liqun Feng (Parkinson's Disease)
We investigate the differential diagnostic value of tremor analysis of EMG on Parkinson’s disease (PD), essential tremor (ET), and enhanced physiological tremor (EPT). Clinical data from 25 patients with PD, 20 patients with ET, and 20 patients with EPT were collected. The tremor frequency and muscle contraction pattern of the resting, posture, and 500 g and 1000 g overload were recorded. The frequency of PD tremor was 4–6 Hz, and the frequency of ET was also in this range; the frequency of EPT is 6–12 hz having some overlap with PD. The muscle contraction patterns of the ET and EPT group were mainly synchronous contraction, and the muscle contraction mode of the PD group was mainly alternating contraction. Having tremor latency from rest to postural position and having changes in tremor amplitude after mental concentration in PD might distinguish ET. Tremor analysis of EMG was able to distinguish PD from ET and EPT by varying the tremor frequency and muscle contraction pattern. It can also differentiate between PD and ET by the latency and concentration effect and ET and EPT by weight load effect.